First clinical experience with a novel, mobile cone-beam CT system for treatment quality assurance in brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Background and purpose: On-site cone-beam computed tomography (CBCT) has gained in importance in adaptive brachytherapy during recent years. Besides treatment planning, there is increased need particularly for image-guidance during interventional procedures and for image-guided treatment quality assurance (QA). For this purpose, an innovative CBCT device was rolled out at our hospital as the first site worldwide. We present the first clinical images and experiences. Materials and methods: The novel CBCT system is constructed of a 121 cm diameter ring gantry, and features a 43.2 × 43.2 cm2 flat-panel detector, wireless remote-control via tablet-PC, and battery-powered maneuverability. Within the first months of clinical operation, we performed CBCT-based treatment QA for a total of 26 patients (8 with breast, 16 with cervix, and 2 with vaginal cancer). CBCT scans were analyzed regarding potential movements of implanted applicators in-situ during the brachytherapy course. Results: With the presented device, treatment QA was feasible for the majority of patients. The CBCT scans of breast patients showed sufficient contrast between implanted catheters and tissue. For gynecologic patients, a distinct visualization of applicators was achieved in general. However, reasonable differentiations of organic soft tissues were not feasible. Conclusion: The CBCT system allowed basic treatment QA measures for breast and gynecologic patients. For image-guidance during interventional brachytherapy procedures, the current image quality is not adequate. Substantial performance enhancements are required for intraoperative image-guidance.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Adaptive brachytherapy; Gynecologic brachytherapy; Image-guidance; Mobile imaging; On-site computed tomography imaging